2006
DOI: 10.1536/ihj.47.855
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Adiponectin Levels and Subclinical Carotid Atherosclerosis in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: SUMMARYThe purpose of this study was to examine the relation between adiponectin levels and subclinical carotid atherosclerosis in patients undergoing coronary artery bypass grafting (CABG). Serum concentrations of adiponectin and carotid intima/media thickness (IMT) were measured in 84 consecutive patients who underwent CABG. Carotid IMT both at the common carotid artery and carotid bulb level was correlated negatively and significantly (r = -0.581 and r = -0.415, respectively, P < 0.01) with the serum concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The inverse correlation between serum adiponectin concentrations and carotid IMT (intima-media thickness), a well-established measure of subclinical atherosclerosis, has been reported in a number of studies in both healthy subjects and patients with T2DM [38,39]. In a study of 140 obese juveniles (mean age, 13.5 years), serum levels of adiponectin were correlated negatively with carotid IMT, even after controlling for BMI, the insulin resistance index, cholesterol, triacylglycerols (triglycerides), blood pressure, hs-CRP (high-sensitivity C-reactive protein), gender and age [40].…”
Section: Clinical Datamentioning
confidence: 90%
“…The inverse correlation between serum adiponectin concentrations and carotid IMT (intima-media thickness), a well-established measure of subclinical atherosclerosis, has been reported in a number of studies in both healthy subjects and patients with T2DM [38,39]. In a study of 140 obese juveniles (mean age, 13.5 years), serum levels of adiponectin were correlated negatively with carotid IMT, even after controlling for BMI, the insulin resistance index, cholesterol, triacylglycerols (triglycerides), blood pressure, hs-CRP (high-sensitivity C-reactive protein), gender and age [40].…”
Section: Clinical Datamentioning
confidence: 90%
“…Hypoadiponectinemia has been correlated with increased atherosclerosis-related compounds, including adipocyte fatty-acid-binding protein (A-FABP), lipocalin-2, as well as other markers of oxidative stress [43,44]. The compound has great potential as a marker for atherosclerotic disease, its decrease having been shown to be predictive of acute coronary syndrome, myocardial infarction, coronary artery disease, and ischemic cerebrovascular disease [45,46].…”
Section: Adiponectinmentioning
confidence: 99%
“…The association between adiponectin and carotid plaques has been investigated in a few studies, but to our knowledge, none has found a significant association 10,11 . In the Health Professionals Study, a doubling of baseline adiponectin level was reported to be associated with a statistically significant 20% reduction in myocardial infarction (MI) risk in multivariate analyses, after adjustment for age, smoking, hypertension history, lipids, glycemic control, and C-reactive protein (CRP) 12 .…”
Section: Original Papermentioning
confidence: 99%